Investasi Wakaf Melalui Cash Waqf Linked Sukuk Ritel Untuk Lingkungan Hijau - Niswatun Hasanah (AMAL: Jurnal Ekonomi Syariah, 2025)
Issues concerning environmental sustainability and environmental health were discussed at the 2022 G20 Summit. Seven priority issues were identified in the Environmental Deputies Meeting (EDM) and three in the Climate Sustainability Working Group (CSWG). Consequently, most countries are currently seeking creative financial solutions to address these issues. One instrument for linking environmental commitments with sustainable government financing is sustainability-linked bonds (SLB).This study aims to identify a model for implementing the mauquf 'alaih (implied) yield series of CWLS for green environmental programs.The method used in this article is a qualitative approach with explanatory analysis using secondary data. Data collection was conducted through journal articles previously searched through Publish or Paris.This article focuses on two issues: Green Sukuk in Indonesia and CWLS for green environmental programs. Several CWLS Series that have been published by the Ministry of Finance, there is the CWLS SWR003 series whose social programs are implemented for a green environment, namely energy security programs and environmental programs that support each other with health programs such as sanitation. This energy security program has been programmed by nadzir (YPM Salman ITB in the form of "Installation of Solar Panels at the Salman ITB Mosque" and a social program for environmental health in the form of Sanitation for the Community (SAUM).